Synergistic Integration of Invasive Alien Species Tradescantia fluminensis Residual Biomass with Commercial Pulp for Enhanced Sustainable Paper Production - Antía Iglesias; Ángeles Cancela (Applied Sciences)
Invasive alien species pose significant ecological challenges, with Tradescantia fluminensis emerging as a major threat in Europe. This study investigates the potential of repurposing biomass from this invasive plant, collected in Galicia, for use in the pulp and paper industry. Following prior research on engineered paper made from Tradescantia fluminensis, this study examines its integration with commercially bleached eucalyptus pulp in varying proportions (90%, 70%, 50%, 30%, 10%). Key structural and physical properties, including pulp drainability, grammage, thickness, specific volume, density, and permeability, were analyzed to evaluate the viability of incorporating Tradescantia fluminensis biomass into paper production. The chemical composition and internal structures were observed using SEM visualization (JEOL 6100) to provide insights into the engineered paper’s characteristics. The findings of this study suggest that blending Tradescantia fluminensis biomass with commercial pulp could provide a sustainable approach to paper manufacturing, leveraging residues from environmental cleanup efforts to reduce reliance on traditional raw materials. The best paper qualities were obtained with medium blends, ranging from 30 to 70% and 70 to 30% biomass to raw material. At these proportions, paper properties remained balanced, integrating both visual and physical characteristics. The most relevant data were observed for drainability (35–33° SR) and air resistance, which ranged from 5.57 to 7.33 s for 300 cm3 using the Gurley method. This study highlights the dual benefits of mitigating the ecological impact of invasive alien species waste while promoting sustainable practices in the paper industry. By challenging conventional norms and exploring new possibilities, it fosters the development of sustainable paper materials capable of promoting climate awareness and strengthening the connection between consumers, materials, and production processes.